Approximation properties of systems of exponentials in one space of analytic functions - Vynnyts’kyi, B. V. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We obtain a criterion of completeness of a system of exponentials in the Hardy-Smirnov spaces in unbounded convex polygons and study the properties of incomplete systems of exponentials.